Metric Characteristics of Tests Assessing Speed and Agility in Youth Soccer Players - Zeljko Kovacevic; Frane Zuvela; Goran Kuvacic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The main aim of this study was to validate the measuring instruments for assessing sprinting speed and specifi c agility in youth soccer players. The study was conducted on a sample of 32 soccer players in younger age categories. The sample of variables included three tests assessing sprinting speed (5-meter sprint from a standing start, 20-meter sprint from a standing start, and fl ying 15-meter sprint), and three tests assessing specifi c agility (slalom run with a ball, zig-zag run with a ball, and 20-meter sprint with a ball). Metric characteristics of tests were determined by calculating indicators of reliability, homogeneity, sensitivity, and factor and pragmatic validity. The values of indicators of metric characteristic showed that the applied motor tests had high level of reliability, good homogeneity, normal distribution of data, and acceptable values of factor and pragmatic validity. As a recommendation for future scientifi c and/or expert activities which would include assessment of speed and specifi c agility in young soccer players, investigations should defi nitely include 20-meter sprint from a standing start and slalom run with a ball.